RESPON PAJAK DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KOTA PALEMBANG - Taufiq Marwa; Abu Kosim (Department of Development Economics, Universitas Sriwijaya, 2004)
This research is aimed to analysing the response of local taxes receipt toward product domestic regional bruto in Palembang. Data of this research are secondary data from 1994-2002 obtained from the publication of outhority institution. The model applied was simple linear regression to evaluated the response of local taxes receipt toward product domestic regional bruto. The results of this research indicated that The elasticity of local taxes receipt toward product domestic regional bruto is less than one (inelastic). Keywords: Response, Local Taxes Receipt, Elasticity, PDRB